Contemporary art in Asia a critical reader - Chiu, Melissa; Genocchio, Benjamin (MIT Press, 2011)
"In 2008, Asia stormed the citadel of the New York art world when two major museums presented retrospectives of Asian contemporary artists: Cai Guo-Qiang at the Guggenheim Museum and Takashi Murakami at the Brooklyn Museum. Meanwhile, in Hong Kong, a painting by Zeng Fanzhi sold for (dollar)9.5 million, setting a new world auction record for Chinese contemporary art. The Western art world is still coming to grips with the challenge: it is all about Asia now. This book is the first anthology of critical writings to map the shift in both the nature and the reception of Asian art over the past twenty years. Offering texts by leading figures in the field (mostly Asian), and including more than fifty illustrations in color and black and white, it covers developments in East Asia (including China, Korea, and Japan), South Asia (including India and Pakistan), and Southeast Asia (including Vietnam, Indonesia, and Thailand). Together, the twenty-three texts posit a historical and pan-Asian response to the question, "What is Asian contemporary art?" Considering such topics as Asian modernism ("productive mistranslation" of the European original), Asian cubism, and the curating, collecting, and criticism of Asian contemporary art, this book promises to be a foundational reference for many years to come." -- Provided by publisher.